Design Thinking and Innovation in Learning. - Taricani, Ellen (Emerald Points Ser., 2021)
Acknowledging that empowering today's learner to find innovative and enriching experiences brings about a deeper desire within them to learn and develop skills, this book showcases a combination of innovative educational practices and creative pedagogy techniques to demonstrate how educators can kick-start learning success.